ANALISIS PERSEPSI DAN PREFERENSI NASABAH MUSLIM DAN NASABAH NON MUSLIM TERHADAP KEPUTUSAN MEMILIH PERBANKAN SYARIAH DI PROVINSI DIY - Kurniati . (Universitas Alma Ata, 2012)
ABSTRACT Led by syariah bangking operating in Indonesiam many banks think that their main affecting the loyalty of customer to syariah banking was the practically consistent obedience to Islamic banking principles. Unfortunately, rhereafter were controversies in regard with this teory. This research had an aim to analyse and for knowing preference and perceptions of individual customer banking Muslim and non Muslim prefer syariah banking in Province DIY. In taking the sample, random sampling is taking. The sample of the study is 163 individual customer syariah banking in Province DIY. Furthermore, descriptive statistic, are used in the study. Keyword: preference and perceptions of customer syariah banking.